2020
DOI: 10.1101/2020.06.11.20128520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 pandemic-related lockdown: response time is more important than its strictness

Abstract: The rapid spread of SARS-CoV-2 and its threat to health systems worldwide have led governments to take acute actions to enforce social distancing. Previous studies used complex epidemiological models to quantify the effect of lockdown policies on infection rates. However, these rely on prior assumptions or on official regulations. Here, we use country-specific reports of daily mobility from people cellular usage to model social distancing. Our data-driven model enabled the extraction of mobility characteristic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…The need for early adoption of containment measures was also demonstrated by Loewenthal et al who found strong correlation between the time at which containment measures were initiated and the number of deaths 27 . Based on their results, delay of 7.49 days in initiating containment measures would result in two-fold increase in the number of deaths.…”
Section: Discussionmentioning
confidence: 78%
“…The need for early adoption of containment measures was also demonstrated by Loewenthal et al who found strong correlation between the time at which containment measures were initiated and the number of deaths 27 . Based on their results, delay of 7.49 days in initiating containment measures would result in two-fold increase in the number of deaths.…”
Section: Discussionmentioning
confidence: 78%
“…The results confirmed the importance of a timely response to the COVID-19 pandemic suggested by previous real-world studies. 12, 13, 19 Belgium, Sweden and UK stood out as the three countries in our study area that, according to our estimates, may have experienced lower excess mortality by intervening earlier. The slow response in Belgium may thus explain an important part of the excess mortality compared with its neighbouring country Netherlands.…”
Section: Discussionmentioning
confidence: 57%
“…According to Loewenthal et al (2020), to reduce the number of deaths is essential to implement confinement policies at a very early stage. If social distancing is not adopted, death incidents are doubled every 7.49 days.…”
Section: Resultsmentioning
confidence: 99%
“…If social distancing is not adopted, death incidents are doubled every 7.49 days. 57 Piguillem et al Early detection of cases through surveillance and aggressive contact tracing around known cases has helped to contain spread of the outbreak in Singapore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation